To cache or not to cache? - Toyad, Andrea (My University, 2026)
Our research will expand previous research on inhibitory control in the North American Red Squirrel (Tamiasciurus hudsonicus). We will investigate inhibitory control through a food selectivity task and post-selectivity (caching) behavior. The selectivity task will explore the selection of a preferred food item (shelled and unshelled peanuts) in order to understand how inhibiting immediate caloric intake may show a level of self control. Both inhabitation of an immediate caloric intake the resulting delay in gratification by caching the food choice, will allow us to provide further evidence that red squirrels can restrict innate feeding responses. Thus, we predict that squirrels will practice inhibition on a prepotent behavior to immediately consume the food, and we predict that squirrels will cache the food further exhibiting a delay of gratification like behaviour. These observations will contribute to existing literature on animal inhibitory control, self control (delay of gratification) and cognitive decisions.
Presented on April 23, 2026, at Student Research Day, held at MacEwan University in Edmonton, AB.
Keywords: North American Red Squirrel; caching; Student Research Day; self control; inhibitory control